Constructing Chongqing Traditional Songs Teaching Guidebook for Vocal Music Students in Chengdu University, Chengdu, Sichuan - Yu, Qi; Banchongsil, Orawan (Journal of Roi Kaensarn Academi, 2023)
Chongqing Traditional songs are an important part of Sichuan Traditional songs. It is a unique kind of song in China. This kind of song is different from art songs and composition songs. It has the basic characteristics of "oral communication", "collective composition" and "local characteristics". The objectives of research were: 1) To study Chongqing Traditional songs in Chengdu for vocal music students. 2) To construct teaching guidebook for Chongqing Traditional songs for vocal music students in Chengdu university. 3) To experiment the Chongqing Traditional songs Teaching guidebook to the vocal music students experimental group. 4) To find out the efficiency of the Chongqing Traditional song guidebook. This research is a comprehensive study, used a mixed method, qualitative and quantitative approach. The population was 10 first year vocal music students in Chengdu University. The study instruments included: Interview forms; Chongqing traditional song teaching guidebook; Performance tests; and IOC forms. Descriptive analysis was used to analyze the interview information from the three key informants and statistical analysis was used to analyze the scores of the performance tests: percentages (%) the formative and summative tests. The results of this study are: (1) Vocal teaching Chongqing traditional songs should make students understand breath, dialect, tone, melody and emotion and follow scientific vocal methods. (2)The guidebook for teaching Chongqing traditional songs consisted of Chapter1 Introduction, Chapter2 How to use the Chongqing traditional songs Teaching Guidebook, Chapter3 Basic Vocal Exercises, Chapter4 Advanced Vocal Exercises, Chapter5 Method of Teaching and songs, Chapter6 Music notation of songs, Chapter7 Lesson plan; (3)The guidebook of Chongqing traditional songs were conducted for the experimental group of students; (4) the efficiency of the guidebook of traditional songs Chongqing was 85/95, which was higher than the hypothesis 80/80, and it can be said that the Chongqing guidebook for traditional songs is effective and can be used for teaching.